The Effect of Motivation on the Learning Achievement - Dewi Ginaib Fitriwati (Indonesian Journal of Integrated English Language Teaching, 2018)
This article discusses the effect of students ' intrinsic motivation on their English achievement, to find out the effect of students’ extrinsic motivation on their English achievement, and to find out the effect of the  eighth grade students’ intrinsic and extrinsic motivation together towards their English achievement at SMPN 5 Bantan. The subject of study was the Eighth grade students of SMPN 5 Bantan  totaling 88 students. The data were collected by using a set of questionnaire and documentation. The instruments used were a reliability test, a normality test and a homogenity test, while the data analysis was used product moment by employing  multiple correlation analysis and regression analysis with a significant level of 5%. The analyzed data werte taken from the  scores of Mid semester. The results showed that 1. There was a positive and significant effect of students' intrinsic motivation on their English learning achievement  with a value of r count was greater than r table (0.287> 0.207). 2. There was no significant effect between students’ extrinsic motivation with their English learning achievement. 3. There was a significant relationship between intrinsic and extrinsic motivation of students with  their English learning achievement  where F count was equal to 6.227, while the F table at 4.88 with N = 88 at the significance level of 5%. So, F was calculated from the F table ( 6.227> 4.88), because the findings of this study showed a significant effect. Overall,  hypothesis test matched the research finding. So, if students have higher motivation, their learning   achievement will increase